Question

# Write down the inference or replacement rule and the line(s) it uses (1) A -> [(AvB)...

Write down the inference or replacement rule and the line(s) it uses

(1) A -> [(AvB) -> (C•D)]
(2) [A • (AvB)] -> (C•D) ______

(1) (A • B) v (~A • B)
(2) (~A • B) v (A •B) _________

(1) (P • Q)
(2) (P • Q) -> ~ (A v B)
(3) ~ (A v B) _________

1) A• (B v C)
(2) [A• (B v C)] v [~A• ~(B v C)] ___________

(1) (A•B) ≡ (C•D)
(2) [((A•B) -> (C•D)] • [(C•D) -> (A•B)] _____________

Use the inference and replacement rules to show that these are valid arguments

(1) ∼R ⋁ P      (p)
(2) ~P ⋁ R    (p) / R ≡ P
(3)
(4)
(5)
(6)

(1) H -> B    (p)
(2) ∼(B · A)   (p) / H -> ~A
(3)
(4)
(5)

(1) A•~~B (p) / ~(~B•~C) • A
(2)
(3)
(4)
(5)
(6)

Use the 18 inference and replacement rules to show that these are valid arguments

(1) ∼R ⋁ P      (p)
(2) R ⋁ ∼P      (p) / R ≡ P
(3)
(4)
(5)
(6)
(7)

(1) C -> (T -> L)      (p)
(2) ~L                     (p)
(3) T                       (p) /~C
(4)
(5)
(6)
(7)
(8)

plz feel free to comment in case of doubts as i am happy to help you. Plz upvote the solution if u r satisfied. It means a lot to me. Thanks

#### Earn Coins

Coins can be redeemed for fabulous gifts.